2008
DOI: 10.1111/j.1365-2044.2008.05676.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of selective decontamination of the digestive tract in United Kingdom intensive care units*

Abstract: SummaryThe use of selective decontamination of the digestive tract (SDD) remains controversial despite several large randomised-controlled trials and meta-analyses. A postal survey of intensive care units in the United Kingdom was conducted to document current use of SDD, and to identify factors influencing this practice. The response rate was 71%. The vast majority (182 units, 95%) do not use SDD mainly because practising clinicians do not believe it works or that there is not enough evidence (51%), and becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…SDD is not widely practiced (Barends et al, 2008, Bastin andRyanna, 2009) or even studied outside the European context. (Kollef, 2000, Misset et al, 1996 The lack of wide adoption of SDD within the regions in which this study was conducted may explain the variability in participants' knowledge observed in the data.…”
Section: Discussionmentioning
confidence: 99%
“…SDD is not widely practiced (Barends et al, 2008, Bastin andRyanna, 2009) or even studied outside the European context. (Kollef, 2000, Misset et al, 1996 The lack of wide adoption of SDD within the regions in which this study was conducted may explain the variability in participants' knowledge observed in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable evidence supporting the benefit of SDD [5][6][7] , adoption internationally is low 9,10 . Amongst proposed reasons for this lack of adoption are controversies surrounding prophylactic use of antibiotics and associated risk of antibiotic resistance 11,12 and purported difficulty of SDD implementation and delivery 13 .…”
Section: Selective Decontamination Of the Digestive Tract (Sdd) Is Anmentioning
confidence: 99%
“…All UK ICUs delivering SDD, identified from a recent national SDD survey 9 , or known by the study investigators to deliver SDD were deemed eligible for inclusion (15 ICUs). Two ICUs were purposively selected to represent recent and more remote lengths of time since SDD adoption and different geographical locations (i.e.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
“…Despite much interest over many years and a large evidence base (36 randomised controlled studies) suggesting efficacy in reducing rates of HAIs and increasing survival [1][2][3][4][5][6][7][8][9] SDD has not been widely adopted into intensive care practice worldwide. SDD continues to be a controversial subject, and seems to receive limited support from clinicians [10,11]. The multinational SuDDICU (Selective Decontamination of the Digestive tract in critically ill patients in Intensive Care Units) mixed-methods research program [12] aimed to establish reasons for the low adoption rate, barriers and facilitators to adoption of SDD and directions for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Few published studies have examined healthcare professionals' views about SDD, and those that have do not use a theoretical framework [11,13]. This lack of a theoretical framework means that findings cannot be used to build a cumulative evidence base or to inform an appropriate direction for future research.…”
Section: Introductionmentioning
confidence: 99%